From script to language: the three identities of ‘Arabic-Tamil’ - Tschacher, Torsten (South Asian history and culture, 2018)
Since at least the eighteenth century, Muslims in southern India and Sri Lanka have been employing the Arabic script to record Tamil texts. Popularly known as ‘Arabic-Tamil’ or ‘Arwi’, this practice has been evaluated in widely divergent manners. While to some, ‘Arabic-Tamil’ is primarily a term reserved for the use of the Arabic script to record Tamil, others perceive it as a different style of Tamil, or even as a completely separate language. Whereas Tamil nationalist discourse has identified ‘Arabic-Tamil’ as a danger to the unity of the Tamil nation, some Muslims celebrate it as the symbol of a separate identity, while yet others lament that ‘Arabic-Tamil’ fails to provide a clean break with Tamil as used by non-Muslims. Even more puzzling is the fact that before the twentieth century, most ‘Arabic-Tamil’ records fail to identify themselves as anything else but ‘Tamil’. This article traces complex histories attaching to the idea of ‘Arabic-Tamil’ to uncover the historical situated-ness of the term and show how it has been linked to political discourses and processes of identity formation throughout the twentieth and twenty-first centuries.
Published online: 20 Dec 2017
Gesehen am 02.11.2023